2007
DOI: 10.1080/09537100600800792
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-induced interleukin 1βsynthesis in platelet suspensions: Impact of contaminating leukocytes

Abstract: A controversial discussion as to whether human platelets are capable of regulated protein synthesis has been ongoing for over half a century. A previous study has suggested that human platelets synthesize large amounts of interleukin 1beta (IL-1beta) in response to external cues and in a physiologically significant manner. However, cytokines such as IL-1beta are generally considered to be products of leukocytes and it could not be completely excluded that contaminating leukocytes may have contributed to the IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…reported that chondrocytes from the native cartilage did not participate in the repopulation of the defect, and that the cartilaginous repair appeared to be mediated by the proliferation and differentiation of mesenchymal cells from the bone marrow32. TNF-α was selected as a pro-inflammatory cytokine, and this protein along with IL-1β are key cytokines associated with the catabolic state observed in OA33, and leukocytes are the primary source of inflammatory cytokines such as IL-1 and TNF-α3435363738. L-PRP contained more leukocytes, TNF-α and IL-1β than P-PRP in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…reported that chondrocytes from the native cartilage did not participate in the repopulation of the defect, and that the cartilaginous repair appeared to be mediated by the proliferation and differentiation of mesenchymal cells from the bone marrow32. TNF-α was selected as a pro-inflammatory cytokine, and this protein along with IL-1β are key cytokines associated with the catabolic state observed in OA33, and leukocytes are the primary source of inflammatory cytokines such as IL-1 and TNF-α3435363738. L-PRP contained more leukocytes, TNF-α and IL-1β than P-PRP in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators attributed a positive outcome to contamination with monocytes, which have a many-fold–higher translation capacity (2224). Therefore, we included a purity check in every experiment to demonstrate unequivocally that platelets synthesize TF.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin activated platelets move IL-1β to their surface(21, 22) where it participates in juxtacrine stimulation of endothelial cells(21), and they secrete small amounts of mature IL-1β(23) that participates in the inflammatory process. These observations have now been challenged with the suggestion that even low numbers of monocytes in platelet preparations are sufficient to account for thrombin-stimulated IL-1β production(24). Assessing contaminating nucleated cells in platelet preparations is difficult(25) when their abundance needs to be less than one per hundred thousand platelets(24).…”
Section: Introductionmentioning
confidence: 99%
“…These observations have now been challenged with the suggestion that even low numbers of monocytes in platelet preparations are sufficient to account for thrombin-stimulated IL-1β production(24). Assessing contaminating nucleated cells in platelet preparations is difficult(25) when their abundance needs to be less than one per hundred thousand platelets(24). This is an important topic given that extreme leukoreduction, on the order of 1 leukocyte per million platelets, is a critical issue in platelet transfusion medicine ((26), and references therein).…”
Section: Introductionmentioning
confidence: 99%